Fundamental Problems Of The Electrodynamics Of Heterogeneous Media With Boundary Conditions Corresponding To The Total-Current Continuity - Grinchik, Nikolay; Grinchik, Nikolay; Korogoda, Oleg; Korogoda, Oleg; Khomich, Mikalai; Ivanova, Svetlana; Terechov, V.I.; Grinchik, Yu.N.; Grinchik, Yu.N. (IntechOpen, 2011)
None